Role of visualization techniques in learning anatomy - A Riju Priyadarshini (National Journal of Clinical Anatomy, 2023)
Anatomy reveals the human body and its architecture. Right from the intricate turn of an artery, loop of a duct, fold of the skin to the microscopic change in epithelium are studied through anatomy. These nuances are appreciated in a precise and accurate manner when a scalpel is laid on one's body. Today, learning anatomy complemented with new age techniques, enables us to visualize a structure along with their surrounding environment.